(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The COVID-19 pandemic caused changes in the educational environment so that the proposed objective is to interpret and conceptualize the learning of mathematics through virtual environments. The methodology of qualitative approach and hermeneutic level, uses the semi-structured interview guide as an instrument. It is concluded that the concepts of learning mathematics through virtual environments in elementary school students consider the acquisition of new progressive knowledge associated with the development of self-knowledge. The skills achieved become skills and abilities that promote self-learning. The elements involved in learning consider didactic resources, active methodology, digital competence and meaningful learning.